Peran CSR Dalam Mereduksi Konflik Korporasi Komunitas Lokal Di Sektor Pertambangan : (Suatu Studi Di Pt Raya, Sumatera Utara - Lubis, Mia Aulina; Fitriyah, Fitriyah (UI Scholars Hub, 2016)
This research deals with A Role of CSR Programs in Reducing Corporate Social Conflict in Mining Industry (A Study in PT. RAYA, Sumatera Utara). This research was conducted on qualitative approach. The data is obtained by literary studies, interviews and observation. Analysis started with describing motivations and conditions of CSR of PT. RAYA since the beginning until the conflicts appeared. Then, the research was trying to look for the CSR implementation strategy, especially as extractive company which undergo conflict with local people and the obstacles that were found by the company as long as they were implementing their CSR, as an interest conflict belong to miners without permissions, negative stigma from the people also intervention and provocation gotten by program receivers.